Peningkatan Keterampilan Membaca Pemahaman Menggunakan Metode Guided Reading - Fitria; Aprizan; Sundahry (CV. DIGITIAL EDUKASI NUSANTARA, 2026)
This study was motivated by the students' low reading comprehension skills; only 7 students (35%) understood the content of the reading material, while the remaining 13 students (65%) did not yet fully grasp it. The objective of this study was to improve reading comprehension skills using the Guided Reading method. A two-cycle Classroom Action Research (CAR) design was employed. The study sample consisted of 20 students. Data were collected through observation, tests, and documentation. The results showed an improvement in teacher performance from 76% in Cycle I to 96% in Cycle II, and an increase in learning mastery from 65% in Cycle I to 85% in Cycle II; specifically, student mastery in reading comprehension rose from 65% in Cycle I to 85% in Cycle II. Guided Reading is a method of guided reading instruction proven capable of enhancing the reading comprehension skills of fourth-grade students at SDN 37/II Pasar Lubuk Landai. This study contributes to the implementation of a reading instruction method that actively engages students through reading activities, teacher guidance, question-and-answer sessions, and discussions to help them better understand reading content. It can be concluded that the implementation of the Guided Reading method is effective in improving the reading comprehension skills of fourth-grade elementary school students. Keywords: Reading Comprehension; Guided Reading; Classroom Action Research